Thyroid Dysfunction in Primary Biliary Cholangitis: A Comparative Study at Two European Centers. (January 2017) - Floreani, Annarosa; Mangini, Chiara; Reig, Anna; Franceschet, Irene; Cazzagon, Nora; Perini, Lisa; Caballería, Llorenç; Cocchio, Silvia; Baldo, Vincenzo; Parés, Albert
Abstract : OBJECTIVES: Primary biliary cholangitis (PBC) is often associated with other autoimmune diseases, but little is known about the influence of thyroid disease (TD) on the natural history of PBC. Our aim is to analyze the association between PBC and TD, and the latter's impact on the natural history of PBC at two European centers. METHODS: The study involved 921 PBC patients enrolled between 1975 and 2015 in Padova (376 patients) and Barcelona (545 patients), with a mean follow‐up of 126.9±91.7 months. Data were recorded on patients' histological stage at diagnosis, biochemical data, associated extrahepatic autoimmune conditions, and clinical events, including hepatic decompensation. RESULTS: A total of 150 patients (16.3%) had TD, including 94 patients (10.2%) with Hashimoto's thyroiditis; 15 (1.6%) with Graves' disease; 22 (2.4%) with multinodular goiter; 7 (0.8%) with thyroid cancer; and 12 (1.3%) with other thyroid conditions. The prevalence of different types of TD was similar in Padova and Barcelona, except for Graves' disease and thyroid cancer, which were more frequent in the Padova cohort (15.7 vs. 5.0%, and 8.6 vs. 1.3%, respectively, P <0.05). Overall, there were no differences between PBC patients with and without TD in terms of their histological stage at diagnosis, hepatic decompensation events, occurrence of HCC, or liver transplantation rate. The presence of associated TD was not associated with lower survival for PBC patients in either cohort. CONCLUSIONS: TDs, and autoimmune TD like Hashimoto's thyroiditis in particular, are often associated with PBC, but the presence of TD does not influence the rate of hepatic complications or the natural history of PBC.